A comprehensive review of acute cardio-renal syndrome: need for novel biomarkers - Dutta, Abhi; Saha, Shubham; Bahl, Ajay; Mittal, Anupam; Basak, Trayambak (Frontiers in Pharmacology, 2023)
Cardiorenal syndrome represents a wide-spectrum disorder involving the heart and kidneys as primarily affected organs. India has an increasingly high burden of acute CRS along with the rise in global statistics. Till 2022, approximately 46.1% of all cardiorenal patients have been diagnosed with acute CRS in India. Acute CRS involves a sudden deterioration of kidney functionalities, referred to as acute kidney injury (AKI) in acute heart failure patients. The pathophysiology of CRS involves hyperactivation of the sympathetic nervous system (SNS), Renin–angiotensin aldosterone system (RAAS) following acute myocardial stress. The pathological phenotype of acute CRS is associated with perturbed inflammatory, cellular, and neurohormonal markers in circulation. These complications increase the risk of mortality in clinically diagnosed acute CRS patients, making it a healthcare burden worldwide. Hence, effective diagnosis and early prevention are crucial to taper off the progression of CRS in AHF patients. Present biomarkers like serum creatinine (sCr), cystatin C (CysC), glomerular filtration rate (GFR), Blood Urea Nitrogen (BUN), Serum and/or urine neutrophil gelatinase-associated lipocalin (NGAL), B-type natriuretic peptide (BNP), NT-proBNP is clinically used to diagnose AKI stages in CRS patients but are limitedly sensitive to early detection of the pathology. Therefore, the need for protein biomarkers is emerging for early intervention in CRS progression. Here, we summarized the cardio-renal nexus in acute CRS with emphasis on the present clinicopathological biomarkers and their limitations. The objective of this review is to draft the need for novel proteomic biomarkers that will curb the burgeoning concern and direct future research trials.